PERNIKAHAN DINI DALAM PERSEKTIF AGAMA ISLAM: SISI POSITIF DAN NEGATIF - Pangestika, Adella Ayu; Nisa, Nabila Luthfiyatun; Hami, Widodo (Al-Usroh, 2024)
This research aims to examine: 1) The positive impact of early marriage from an Islamic religious perspective; 2) The negative impact of early marriage; and 3) Factors that cause early marriage to occur. Using qualitative research methods with a literature study approach, this research collects data from relevant previous research. Data is compiled, analyzed and concluded to provide a comprehensive picture of early marriage. The research results show that: 1) There are positive impacts such as avoiding promiscuity; 2) Negative impacts include psychological and health problems; 3) Factors that influence include economics, tradition, and low level of education.